Resilient entrepreneurs? Revisiting the relationship between the Big Five and self-employment - Petrik Runst; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
Based on a trait-oriented approach, Big Five personality traits have been repeatedly shown to affect entrepreneurial action. In the last two decades, a new literature stream on the Big Five has emerged in the field of psychology that has partly moved away from a traitbased perspective towards a person-centered approach, suggesting that multiple stable combinations of traits form individual personalities. We examine the relationship between this prototyping approach and entrepreneurship. Moreover, we compare prototyping with entrepreneurial profiling, another person-oriented approach to the Big Five, which assumes that low levels of agreeableness and high levels of all other traits describe a particular entrepreneurship-prone personality. By using data from the German Socio-Economic Panel (SOEP), we show that at least three prototypes can be identified, one of which - the resilient type - can be hypothesized to significantly increase the likelihood of entrepreneurial action. Our regression results provide evidence of a positive impact of the resilient type on the likelihood of and transitioning into self-employment but not the likelihood of exit. We also show that the prototyping approach explains individual self-employment decisions over and above what can already be explained by the profiling approach. Thus, the entrepreneurial profile tends to ignore a relatively large number of individuals who exhibit certain combinations of traits predisposing them to become entrepreneurs. In the context of entrepreneurship, profiling should therefore only be seen as a first step on the way from the usual trait-based to a person-oriented view of the Big Five.
Keywords: D91; L26; M13; 330; Entrepreneurship; Self-employment; Big Five; Personality; Prototypes; Profiles